Evaluation of interprofessional care processes for patients treated with oral anticancer drugs. - Kinnaer, Lise-Marie; Kenis, Ilyse; Foulon, Veerle; Van Hecke, Ann (Journal of Interprofessional Care)
Information on interprofessional team composition and functioning in the care for patients on oral anticancer drugs (OACDs), and how healthcare professionals (HCPs) evaluate in-hospital care processes is scarce. We aimed to investigate interprofessional care processes for OACD-patients in a partially mixed-methods study. A combination of (a) the CareProces Self-Evaluation Tool (CPSET), completed by HCP-team members by health profession who were either currently involved in care processes (oncologists and nurses) or potentially involved in future care (pharmacists, psychologists, social workers), and by hospital managers (N = 87) and (b) semi-structured interviews in a subsample of oncologists, nursing staff, and pharmacists (N = 26) were used. Care process coordination was evaluated poorly, mainly by nurses, pharmacists, and psychologists. Nurses and pharmacists believed that they were not engaged in the organization of OACD care, lacked role clarity, and perceived no meaningful interprofessional practice. HCPs had different perceptions toward timing and planning of patient education and follow-up. Monitoring of care processes occurred only occasionally and was unstructured resulting in apoor complication-management and variance within care processes. Care processes for OACD-patients showed opportunities for optimization of interprofessional practice in timing, planning, and monitoring. Rethinking care processes through co-design is needed.